Analysis of endometrial biopsy reports from adult women with abnormal uterine bleeding, a cross-sectional descriptive study - Keshta, Mohamed S.; Keshta, Ahmed S.; Husain, Manar; Gomaa, Hoda N.; Ehiwario, Jennifer; Gupta, Alka; Jeddy, Rafiea (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Abnormal uterine bleeding is a common complaint in most women of different ages that prompts seeking gynecologic care. This study aimed to analyze and age-classify the prevalence of endometrial pathologies in women with abnormal uterine bleeding. Methods: This is a cross-sectional and a descriptive study, conducted at the obstetrics and gynecology department of the American Mission Hospital in the Kingdom of Bahrain on 88 patients who presented with abnormal uterine bleeding between January 2019 and January 2020. Results: Eighty-eight women with abnormal uterine bleeding demonstrated a fluctuating pattern of twenty endometrial pathologies distributed among five age groups in the range of 30-71. The mean age of the study cohort was 44.9±7.65 years; 55% of which were reported in the 41-50 age group. Benign endometrial polyp was reported as the most common pathology, accounting for 47.8% of the cohort. Although benign endometrial polyp was significantly the highest overall finding in all three age groups younger than 60, disordered proliferative endometrium was the highest reported single pathology in the age group 41-50, (N=10, p≤0.0001). Conclusions: This study demonstrated that benign endometrial polyp was the most common finding in women with abnormal uterine bleeding. This information could be essential for patient guidance and awareness of the benefits of endometrial biopsy. Eventually, the prediction of the potential endometrial pathology in women with abnormal uterine bleeding is vital for early disease management.